Polystyrene nanofiber materials modified with an externally bound porphyrin photosensitizer - Henke, Petr; Lang, Kamil; Kubát, Pavel; Sýkora, Jan; Slouf, Miroslav; Mosinger, Jiří (ACS applied materials & interfaces, 2013)
Polystyrene ion-exchange nanofiber materials with large surface areas and adsorption capacities were prepared by electrospinning followed by the sulfonation and adsorption of a cationic 5,10,15,20-tetrakis(1-methylpyridinium-4-yl)porphyrin (TMPyP) photosensitizer on the nanofiber surfaces. The morphology, structure, and photophysical properties of these nanofiber materials were characterized by microscopic methods and steady-state and time-resolved fluorescence and absorption spectroscopies. The externally bound TMPyP can be excited by visible light to form triplet states and singlet oxygen O2((1)Δg) and singlet oxygen-sensitized delayed fluorescence (SODF). The photophysical properties of the nanofibers were strongly dependent on the amount of bound TMPyP molecules and their organization on the nanofiber surfaces. The nanofibers demonstrated photooxidative activity toward inorganic and organic molecules and antibacterial activity against E. coli due to the sensitized formation of O2((1)Δg) that is an effective oxidation/cytotoxic agent. The nanofiber materials also adsorbed heavy metal cations (Pb(2+)) and removed them from the water environment.
Keywords: fotosenzibilizující látky; Polystyrenes; olovo; Photosensitizing Agents; singletový kyslík; Escherichia coli; Lead; Nanofibers; antibakteriální látky; Adsorption; Porphyrins; nanovlákna; Anti-Bacterial Agents; polystyreny; Water Pollutants, Chemical; porfyriny; Singlet Oxygen; adsorpce; ionty; Ions; chemické látky znečišťující vodu